E-learning Competencies of the Lecturers at Koya University and its Relationship with Some Variables* - Abdul-Rahman, Jabbar Ahmed; Abdullah, Zhwan dalshad (Journal of University of Human Development, 2017)
Knowing the ability and willingness of lecturers in using technology tasks is a key competency, necessary for learning and teaching. This study aimed to explore the list of e-learning competencies that university lecturers should have, and identify the availability of e-learning competencies of Koya University lecturers. The results revealed that e-learning competencies achieved good level among Koya University teaching staff, and also found no statistically significant differences between male and female lecturers in their e-learning competencies. The faculty of Engineering outweighs both faculties of Humanities and Education, and the faculty of Science and Health outweigh the faculty of Humanities in their e-learning competencies. Additionally, there were no significant differences between lecturers according to academic ranks in their e-learning competencies.